Pengaruh Kualitas Pelayanan dan Promosi Terhadap Minat Beli Ulang Konsumen - Heri Winarto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research has an impact on the service sector business which is currently booming. Service businesses must have a certain strategy in order to be able to provide progress towards achievement because of the many service competitors they face. Therefore the quality of service and promotion is very influential in attracting consumer repurchase interest. The rapid development of the business world has had an impact on business progress. Currently, modern marketing strategies use more self-service systems. This research was conducted to determine how much influence service quality and promotion have on consumer repurchase intentions. The research method used is quantitative research. Data analysis techniques using multiple linear regression and classical assumption test. Respondents in this study were consumers, totaling 95 people. The sampling technique used purposive sampling with the criteria that the respondent had visited at least 1 time and had made a repeat purchase. The results showed that service quality and promotion had a significant effect both partially and simultaneously on consumer repurchase intentions in the service sector. The results of the correlation between the independent variables, namely service quality and promotion, are able to explain the dependent variable repurchase intention of 59.2% and the remaining 40.8% is influenced by other factors or by other variables not examined in this study.